Reduced MAGI3 level by HPV18E6 contributes to Wnt/β‐catenin signaling activation and cervical cancer progression - Zhuoli Yang; Hua Liu; Ran Song; Wenxiu Lu; Haibo Wang; Siyu Gu; Xuedi Cao; Yibin Chen; Jihuan Liang; Qiong Qin; Xiaomei Yang; Duiping Feng; et al. (FEBS Open Bio, 2021)
Human papillomavirus type 18 (HPV18) has high carcinogenic power in invasive cervical cancer (ICC) development. However, the underlying mechanism remains elusive. The carcinogenic properties of HPV18 require the PDZ‐binding motif of its E6 oncoprotein (HPV18 E6) to degrade its target PSD95/Dlg/ZO‐1 (PDZ) proteins. In this study, we demonstrated that the PDZ protein membrane‐associated guanylate kinase, WW and PDZ domain containing 3 (MAGI3) inhibited the Wnt/β‐catenin pathway, and subsequently cervical cancer (CC) cell migration and invasion, via decreasing β‐catenin levels. By reducing MAGI3 protein levels, HPV18 E6 promoted CC cell migration and invasion through activation of Wnt/β‐catenin signaling. Furthermore, HPV18 rather than HPV16 was preferentially associated with the downregulation of MAGI3 and activation of the Wnt/β‐catenin pathway in CC. These findings shed light on the mechanism that gives HPV18 its high carcinogenic potential in CC progression.